MISKLASIFIKASI HUBUNGAN KERJA PENGEMUDI OJEK ONLINE (PLATFORM WORKER) DI INDONESIA - Oey, Williams (Faculty of Law, Parahyangan Catholic University, 2024)
Technological developments through digital platforms have created a new work ecosystem, allowing platform workers, such as online motorcycle drivers in Indonesia, to affiliate with various companies to provide transportation services. However, despite these advances, online riders have not received adequate rights protection as ‘workers’ because their status is limited to ‘partners’ (independent contractors) under the Partnership Agreement they sign. This article uses a normative approach to examine how legal developments in Indonesia can classify and protect online riders as workers under employment laws. A comparative approach is employed, referencing policies in Europe, particularly Spain and the European Union, which have been more progressive in interpreting employment relationships for platform workers. The research finds that legal reforms in Indonesia still inadequately protect online riders’ labor rights due to narrow interpretations of employment relationships that fail to keep pace with current developments.